Avaliação do reconhecimento e nomeação de faces famosas em população brasileira - Caíssa Bezerra de andrade (2022)
The human face is the main feature used to identify a person. This feature is so important that subtle differences between faces within the same ethnic group are enough to identify a familiar face among hundreds of unfamiliar faces. Face recognition neural processing is very specialized which makes it possible to identify familiar faces even in blurry images and caricatures, in which the individual’s features can be extremely distorted. Facial recognition and naming have great importance in the social life of individuals and therefore, several researches with recognition tests and naming of famous faces have been conducted in several countries. Through this type of instrument, it is possible to assess, for example, the presence of prosopagnosia and the difficulty in remembering proper names in patients with aphasia, cognitive impairment and dementia syndromes. This work aims to present a test of recognition and naming of famous faces designed for the Brazilian population and to investigate the performance of patients with primary progressive aphasia (PPA), patients with Alzheimer's disease (AD) and cognitively healthy individuals in the test. The test consists of photographs of 15 famous people, including religious, sportsmen, singers, politicians, actors and television hosts, all well known by the general Brazilian population. The test is done in two steps, first, the individual must visualize the image and name it. If individuals cannot name the figure, they are oriented to say the semantic characteristics of the famous person. A total of 247 individuals were evaluated, divided into three groups, 183 from the control group, 31 individuals with AD and 33 with PPA. The study indicates a worse performance of individuals with AD and PPA in the naming of famous people when compared to the control group, with no statistical difference between the groups of individuals with dementia syndromes. Regarding face recognition, there was no statistically significant difference between the performance of individuals with Alzheimer's disease and primary progressive aphasia. A limitation of the study is the non-evaluation of healthy individuals regarding their performance only in face recognition. The instrument for the recognition and naming of famous faces presented in this study is a simple and quick test to be used by researchers and health professionals as a part of the evaluation of patients and the battery of neuropsychological tests.